1979
DOI: 10.1080/713857101
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Bacteriophage Lambda by Combined X-ray and U.V.-light Exposure

Abstract: Extracellular phage lambda has been successively exposed to X-rays and U.V. light. The plaque-forming ability of the irradiated phages was determined on host cells with different repair capacities. No change in sensitivity was found with a pre-treatment of one type of radiation to lethal damage inflicted by the other. This indicates that a prerequisite for an interaction of different types of radiation is either an active metabolism or repair process occurring during the two radiation exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Most of the early work investigating the carriage of two or more prophages was performed with host cells that acquired two prophages at the initial point of infection. However, in experiments performed by Arber, it was demonstrated that the frequency of lambda superinfection events of a lambda lysogen could be increased by the irradiation of the infecting phage (4), which is likely to have favored subsequent integration/recombination events through the activation of DNA repair mechanisms in the host cell (17). In the current study, the lom gene, which has no role in the bacteriophage life cycle (6), was replaced with a spectinomycin resistance cassette, aadA, via recombineering technology (11).…”
mentioning
confidence: 99%
“…Most of the early work investigating the carriage of two or more prophages was performed with host cells that acquired two prophages at the initial point of infection. However, in experiments performed by Arber, it was demonstrated that the frequency of lambda superinfection events of a lambda lysogen could be increased by the irradiation of the infecting phage (4), which is likely to have favored subsequent integration/recombination events through the activation of DNA repair mechanisms in the host cell (17). In the current study, the lom gene, which has no role in the bacteriophage life cycle (6), was replaced with a spectinomycin resistance cassette, aadA, via recombineering technology (11).…”
mentioning
confidence: 99%